PENYULUHAN ES KRIM RUMPUT LAUT (Eucheuma cottonii) BAGI ANAK DAN REMAJA DI JEMAAT GKMI AMBON - Lalopua, Vonda; Gaspersz, Febe (Balobe: Jurnal Pengabdian Masyarakat, 2023)
Seaweed grows and is spread throughout the waters in Indonesia, including in Maluku. Seaweed is a raw material for the food industry and has been used for various ready-to-eat foods such as ice cream. Seaweed is rich in nutrients. Apart from that, the carrageenan contained in Eucheuma cottoni seaweed acts as a stabilizer to prevent the formation of ice crystals and produces a soft ice cream texture. The use of seaweed as processed food, especially ice cream, is not widely known to the public, therefore it is necessary to carry out outreach activities to introduce seaweed ice cream to the target audience of school age children and teenagers so that knowledge about the diversification of processed seaweed increases. Counseling is carried out using the lecture method and participants' responses are measured by carrying out a liking test. The results of the lectures given showed the great interest in seaweed ice cream. The liking test showed that 75% of participants really liked the organoleptic seaweed ice cream, which shows that seaweed ice cream is acceptable and has the potential to be widely developed.